Immunocytochemical Detection of Glutathione S-Transferase in Peripheral Blood Lymphocytes of Rheumatoid Arthritis Patients - Ghazi, Haider F.; Al-Obaidi, Asmaa B.; Adnan, Huda; Habib, Manal A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Peripheral blood lymphocytes (PBL)of Rheumatoid arthritis (RA)patients have a property of phenotypic and functional activation. Glutathione S- transferase pi (GSTπ) has been implicated in playing an important role in the initiation and progression of cellular activation.Objectives: To determine the percentage of cellular expression of GSTπ in the lymphocytes of RA patients in comparison with controls and to explore the relation between its cellular expression and disease activity pattern.Patients and Methods: This prospective study included46 RA patients and 17 healthy controls. Blood samples were taken and from all subjects PBL were isolated and then smeared on slides. The cellular reactivity for GSTπ was determined by immunocytochemistry technique.Results: This study found lower expression of GSTπ in the RA patients with a statistical significant difference with control group, while no statistical difference was found in RA with high and minimum disease activity groups. No correlation was observed between GSTπ with Disease Activity Score (DAS).Conclusion: Although the decrease in the expression of GSTπ in PBLs was pronounced in RA patients, however it doesn’t correlate with disease activity state.